2017
DOI: 10.5194/hess-2017-344
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The challenge of forecasting impacts of flash floods: test of a simplified hydraulic approach and validation based on insurance claim data

Abstract: Abstract. Up to now, flash flood monitoring and forecasting systems, based on rainfall radar measurements and distributed rainfall-runoff models, generally aimed at estimating flood magnitudes - typically discharges or return periods – at selected river cross-sections. The approach presented here goes one step ahead by proposing an integrated forecasting chain for the direct assessment of flash flood possible impacts on inhabited areas (number of buildings at risk in the presented case studies). The proposed a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…The method deriving the flow discharge on the basis of the empirically generated rating curve has been widely used in some steep ungauged catchments (Bihan et al, ; Gaume et al, ; Ran et al, ). The calibration subsets, which consist of 420 observed discharges (Figures and ), were applied for the estimation of the rating curve parameters (Table ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The method deriving the flow discharge on the basis of the empirically generated rating curve has been widely used in some steep ungauged catchments (Bihan et al, ; Gaume et al, ; Ran et al, ). The calibration subsets, which consist of 420 observed discharges (Figures and ), were applied for the estimation of the rating curve parameters (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that understanding and characterizing dynamic processes in fluid density and flow regimes during a large flash flood is important for hydraulic analysis and prediction of flash floods, as well as for risk assessment (Trieste, ; Lumbroso & Gaume, ; Asano & Uchida, ; Ran et al, ; Bihan et al, ; Cui, Guo, et al, ). When discharge and water level increased in a steep mountain channel, supercritical flow could occur and even destabilize this channel (Church & Zimmermann, ; Ohtsu, Yasuda, & Takahashi, ; Stolle et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature describes impact forecasting approaches for near‐real‐time applications, that is, providing information at the same time as the event is happening (Kim et al, 2011; Kron et al, 2010) and for short‐term forecasts with lead times of a few hours to 1 day. Examples are found in Bihan et al (2017) and Ritter et al (2020) for flash floods and in Bhola et al (2018) and Fuchs et al (2017) for pluvial floods in urban areas. River flood impact forecasting systems with lead times of several days have been proposed by Dottori et al (2017), Bachmann et al (2016), or Brown et al (2016).…”
Section: State Of the Art Of Impact Forecastingmentioning
confidence: 92%
“…Quantitative impact forecasts include estimates of the number of people affected, economic damage, and infrastructure affected. The level of detail varies from the number of buildings affected (Bihan et al, 2017) to economic damage for residential buildings, commerce, agriculture, industry, and transport and infrastructure sectors (Dale et al, 2014; Dottori et al, 2017; Ritter et al, 2020) and economic damage to individual buildings (Dale et al, 2014; Fuchs et al, 2017).…”
Section: State Of the Art Of Impact Forecastingmentioning
confidence: 99%